The effect of live selling promotions and discounts on impulsive buying among generation Z for fashion products on Tiktok Shop Indonesia, with fear of missing out (FOMO) as a mediating variable - Nurul Adilawati; Ika Diyah Candra Arifah; Ratih Amelia; Dhiyan Septa Wihara (Universitas Nusa Cendana, 2026)
The rapid expansion of TikTok Shop has transformed consumer purchasing behavior, particularly among Generation Z, by fostering a highly interactive and psychologically driven online shopping environment. This study investigates the effects of live selling promotions and discounts on impulsive buying behavior, with Fear of Missing Out (FOMO) serving as a mediating variable among Generation Z consumers in Indonesia. Using an explanatory quantitative approach, data were collected through an online questionnaire from 100 Generation Z TikTok Shop users and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that live selling promotions do not directly influence impulsive buying but significantly increase consumers’ FOMO. Discounts exert a significant positive effect on both FOMO and impulsive purchasing behavior. Moreover, FOMO is found to be a strong predictor of impulsive buying and significantly mediates the relationships between live selling promotions, discounts, and impulsive purchasing behavior. These results highlight the pivotal role of psychological mechanisms in shaping Generation Z’s purchasing decisions within social commerce platforms. The study contributes to the growing literature on social commerce and consumer behavior by demonstrating that marketing strategies on TikTok Shop are more effective when they trigger consumers’ perceived urgency and social desirability, rather than solely relying on promotional stimuli. The findings also provide practical implications for digital marketers seeking to enhance consumer engagement and purchase intentions in the Indonesian e-commerce landscape. Keywords: Live Selling Promotion; Discount; FOMO; Impulsive Buying; Generation Z